A cross sectional study on stress and its determinants among doctors in Tirunelveli district, Tamil Nadu - Vellaidurai, Sundari; Krishnan, Rajendran Araneri; Udayakumar, Arun Jayakumar; Siva, Deepapriya (International Journal Of Community Medicine And Public Health, 2024)
Background: Doctors routinely work in a highly stressful environment where death and adverse health outcome are the most common events. This study helps to estimate the prevalence of stress and to determine the stress influencing and relieving factors among doctors in Tirunelveli district. Methods: A cross sectional study conducted among 200 doctors working in Government and Private Hospitals of Tirunelveli District, were selected by simple random sampling. Data was collected using pretested questionnaire and Perceived Stress Scale (PSS-10) was used to assess the stress score. Analysis was done by using SPSS version26. Results: Among the 200 participants, 97 (48.50%) were males and 103 (51.50%) females. Mean PSS score was 23.21±7.74. Moderate stress reported in 116 (58%) study participants, 67 (33.50%) participants have high stress and 17 (8.50%) have low stress. There was statistically significant association between stress and lack of sleep less than 6 hours per day (p=0.005). The main stress influencing factors were working environment (39%) and public behaviour (28%). Conclusions: To prevent potentially fatal medical errors, doctors under stress should receive appropriate counselling, adequate sleep, and maintain regular communication with administrative staff.